When West Met East : Gandharan Art Revisited - Bopearachchi, Osmund (Brill | Manohar Publishers & Distributors, 2020)
When West Met East: Gandhāran Art Revisited is based on hitherto unpublished or partly published sculptures and artefacts from Gandhāra and Greater Gandhāra dispersed in public and private collections across Asia, Europe, and the United States. Its subject is a form of figurative sculpture that emerged in the Gandhāran region between the second and fifth centuries ce and reflects regional cross-cultural elements arising from its direct relationship with Buddhism and to some extent Hinduism, as both flourished in India at the time of the Ku]sā]n Empire. The author's 'Introduction' presents the historical foundation of the innovative artistic expressions that characterize the singularity of Gandhāran art. The first chapter covers the cross-fertilized nature of the art and examines how Western artistic inspirations were transformed into new forms of art to narrate stories of Indian origin. The second chapter argues that Gandhāran artists followed the chronological sequence established in the Sanskrit Lalitavistara, or pre-existing texts which may have inspired this sacred book, when depicting the scenes of the life of the Blessed One starting with the descent of the future Buddha from Tu]sita Heaven up to the first sermon in the deer park. Singling out one particular episode in the Buddha's life, the descent from the Trāyastri`mśa Heaven to Sā`mkāśya, the third chapter focuses on the literary sources that inspired Gandhāran artists. The fourth chapter addresses the question of the first depictions of the Bodhisattvas Maitreya and Avalokiteśvara in Gandhāran art. And, finally, the fifth chapter looks at the symbolism behind the presence of Hindu gods in Gandhāran art.